Synergies in Operational Oceanography: The Intrinsic Need for Sustained Ocean Observations - Davidson, Fraser; Alvera-Azcárate, Aida; Barth, Alexander; Brassington, Gary B.; Chassignet, Eric P.; Clementi, Emanuela; De Mey-Frémaux, Pierre; Divakaran, Prasanth; Harris, Christopher; Hernandez, Fabrice; Hogan, Patrick; Hole, Lars R.; et al. (Frontiers in Marine Science, 2019)
Operational oceanography can be described as the provision of routine oceanographic information needed for decision-making purposes. It is dependent upon sustained research and development through the end-to-end framework of an operational service, from observation collection to delivery mechanisms. The core components of operational oceanographic systems are a multi-platform observation network, a data management system, a data assimilative prediction system, and a dissemination/accessibility system. These are interdependent, necessitating communication and exchange between them, and together provide the mechanism through which a clear picture of ocean conditions, in the past, present, and future, can be seen. Ocean observations play a critical role in all aspects of operational oceanography, not only for assimilation but as part of the research cycle, and for verification and validation of products. Data assimilative prediction systems are advancing at a fast pace, in tandem with improved science and the growth in computing power. To make best use of the system capability these advances would be matched by equivalent advances in operational observation coverage. This synergy between the prediction and observation systems underpins the quality of products available to stakeholders, and justifies the need for sustained ocean observations. In this white paper, the components of an operational oceanographic system are described, highlighting the critical role of ocean observations, and how the operational systems will evolve over the next decade to improve the characterization of ocean conditions, including at finer spatial and temporal scales.